Shapes: Seeing and doing with shape grammars - Reis, J. (2022 17th Iberian Conference on Information Systems and Technologies (CISTI), 2022)
This paper describes the visual interface of a configurable and extensible system to support generic work with shape grammars. Shape grammars allow the implementation of computational mechanisms to analyze and synthesize designs of visual languages and have been used to represent the knowledge behind the creative work of architects, designers and artists. This kind of grammars is inherently visual. The system described, a kind of universal machine for shape grammars, allows users to build their own shape grammars and experiment with them. It has been the focus of our past work, it mixes technological and artistic aspects and it has a specific computational architecture which includes a symbolic and a visual interface. The latter one is the subject of this paper.